(untitled) (The Agriculturists, 2015)
The experiment was conducted at the farmer`s field of Boyerchor, Hatia, Noakhali under On-Farm Research Division, Bangladesh Agricultural Research Institute (BARI), during the rabi seasons of 2011-2013 to study the effect of variety on the productivity of fenugreek in coastal saline soil. The experimental treatments included 3 varieties viz. V1= BARI Methi 1, V2 = BARI Methi 2, V3 = Local Methi. The experiment was laid out in a randomized complete block design with six dispersed replications. There was a strong varietal influence on crop growth and seed yield. Among the varieties, BARI Methi 2 showed the best results in terms of plant height, number of branches, number of pods and number of seeds pod-1 resulting in the highest seed yield of 1497 kg ha-1. It was also observed that plant mortality of fenugreek was highly affected at germination stage when the soil salinity was above 4 dSm-1. However, at the later stages of crop growth up to the maturity, the salt tolerance of the crop was higher varying from 4-12 dSm-1. It was indicated that critical range of salinity level for cultivation of fenugreek was 3.42-12.2 dSm-1 from germination till to maturity. Among the fenugreek varieties, BARI Methi 2 offered the highest net return of Tk. 50150 coupled with a benefit cost ratio of 3.03. Though total cost was the same, BARI Methi 2 showed higher BCR (3.03) over BARI Methi 1 and local Methi due to yield differences. The Agriculturists 2014; 12(2) 18-23